Control Of Utility Interfaces In Low-voltage Microgrids - Tenti, Paolo (2015)
This paper presents a general control technique for utility interactive inverters in low-voltage microgrids. The Utility Interface (UI) is a three-phase power conversion unit, equipped with energy storage, which governs the interaction between the utility grid and the microgrid. The UI is in charge of several functions: in grid-connected operation, it performs as a voltage-supporting unit and compensates the reactive power, unbalance, and distortion caused by loads, whereas in islanded operation, it performs as a voltage- forming unit and sets the voltage and frequency for the entire microgrid. Moreover, the UI ensures seamless transitions from grid-connected to islanded operation and actively decouples the microgrid and the mains. Finally, the UI can perform as a centralized microgrid controller for distributed energy resources. The UI is therefore a crucial component, which needs to be analyzed carefully to ensure safe and reliable operation for the microgrid. This paper discusses a control approach that provides all required functionalities and ensures proper microgrid operation even in case of non- intentional islanding or severe load transients. The experimental results show the behavior of the system in different scenarios.